Republic of Belarus : Staff Report for the 2004 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2004)
This 2004 Article IV Consultation highlights that macroeconomic developments in Belarus in 2003 were mixed. Although in real terms GDP, industrial production, and agriculture all grew by 6.8 percent; according to official data prepared on Belarusian national methodology growth, would be lower on international methodology. Fiscal policy was fairly tight during 2003, mainly owing to limited sources of available financing, such as privatization proceeds. The outlook for 2004 is uncertain. Under current policies, inflation is expected to reach about 22 percent, and real GDP growth is likely to slow to about 4 3/4 percent.